Hadrian's Wall - Wilmott, Tony; Wilmott, Tony (English Heritage, 2012)
From 1976 to 2000 English Heritage archaeologists undertook excavation and research on Hadrian's Wall. This book reports on these findings and includes the first publication, of the James Irwin Coates archive of drawings of Hadrian' Wall made in 1877?96